Deskripsi Kemampuan Berpikir Reflektif dalam Menyelesaikan Soal High Order Thinking Skill (HOTS) ditinjau dari Kecerdasan Logis Matematis Siswa - Hamzah Upu; Rusli; Yuilia Pratiwi (Issues in Mathematics Education (IMED), 2021)
This research was intended to describe student’s reflection thinking ability on solving HOTS questions based on students logical mathematical intelligence. This study was descriptive research with qualitative approach. Subjects of this study were ninth grader students of middle school, consisting of one student with high logical mathematical intelligence, one student with moderate logical mathematical intelligence, one student with low logical mathematical intelligence. Instruments in this study were logical mathematical intelligence test, high order thinking skill questions, and interview guideline. For reflective thinking ability, there are three phases that must be through by students. They are reacting, comparing, and contemplating phases. Research result showed that: 1) For reacting phase; students with high, moderate, and low logical mathematical intelligence fulfilled each indicator to react with their personal understanding. 2) For comparing phase; students with high and moderate logical mathematical intelligence fulfilled each indicator by analysing and evaluating their existing knowledge; student with low logical mathematical intelligence doesn’t meet any indicators. 3) For Contemplating phase; student with high logical mathematical intelligence fulfilled each indicator by solving the questions referring to the knowledge that she remembered; students with moderate and low logical mathematical intelligence don’t meet any indicators.